Role of Schooling and Comprehensive Sexuality Education in Reducing HIV and Pregnancy Among Adolescents in South Africa. (1st July 2022) - George, Gavin; Beckett, Sean; Reddy, Tarylee; Govender, Kaymarlin; Cawood, Cherie; Khanyile, David; Kharsany, Ayesha B.M.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Comprehensive sexuality education (CSE) seeks to reduce risky sexual behaviour and subsequent incidence of unintended pregnancy and HIV among schoolgoing adolescents. This study estimates the association between exposure to CSE and key biomedical and behavioural indicators among adolescent girls in South Africa. Setting: Four DREAMS implementation districts in Gauteng and KwaZulu-Natal provinces in South Africa. Methods: Data from a household-based representative sample of adolescent girls (between the ages 12–18 years) (n = 9673) was collected. Independent variables included school attendance and exposure to CSE, with outcome variables measuring prevalence of HIV, pregnancy, and sexual risky behaviour, including condom use, incidence of age-disparate relationships, and transactional sex. Results: Adolescent girls in school and who had attended CSE classes in the previous 12 months were associated with reduced adjusted odds of being HIV-positive [full sample: adjusted odds ratios (AOR): 0.76, 95% confidence interval [CI]: 0.61 to 0.95, P < 0.05; sexually active sample: AOR: 0.62, 95% CI: 0.40 to 0.96, P < 0.05]. Those in school who attended CSE in the previous 12 months were also more likely to get tested for HIV (AOR: 1.48, 95% CI: 1.32 to 1.65, P < 0.001). Conclusions: The results indicate that school attendance and exposure to CSE is associated with a reduction in risky sexual behaviour. Exposure to CSE is also associated with increased access to HIV testing for adolescent girls both in and out of school. Keeping adolescent girls in school produces the greatest positive sexual behavioural effect; this, coupled with the delivery of quality CSE, is a key strategy for reducing HIV risk.